Effect of deformation degree during drawing out on the quality of heavy-duty hook forgings - Kolisnyk , K. D. (Theory and Practice of Metallurgy, 2026)
This study investigates the influence of the degree of deformation during the drawing out forging operation on the distribution pattern of plastic strain in billets intended for manufacturing high-capacity lifting hooks. The primary objective is to determine the optimal deformation degree that enhances the uniformity of plastic strain distribution across the forging's cross-section. The research was conducted using numerical modeling of the sequential upsetting and drawing out processes, accounting for the continuity of the technological cycle. Drawing out was performed using the "ring" method (circumferential rotation) with a rotation angle of 15° and a relative feed of 0.5. Three deformation degrees per pass were analyzed: 10%, 15%, and 20%. To quantitatively assess strain uniformity, the nonuniformity coefficient Cn was employed, defined as the ratio of equivalent strain values at control points to the maximum equivalent strain within the cross-section. It was established that increasing the deformation degree from 10% to 20% raises the level of accumulated plastic strain and improves its uniformity across the cross-section. The most uniform strain distribution was achieved at a deformation degree of 20%, where the minimum nonuniformity coefficient value was 0.54. This indicates a 46% reduction in strain nonuniformity (since Cn=0.54 corresponds to nonuniformity reduced to 54% of the reference maximum difference). The obtained results can be applied in the development of rational technological regimes for forging high-capacity lifting hooks with enhanced requirements for quality and reliability.